(untitled) - Hopkirk, Peter (John Murray Pubs Limited, 2006)
'Let us turn our faces towards Asia', exhorted Lenin when the long-awaited revolution in Europe failed to materialize. 'The East will help us conquer the West.' Peter Hopkirk's book tells for the first time the story of the Bolshevik attempt to set the East ablaze with the heady new gospel of Marxism. Lenin's dream was to liberate the whole of Asia, but his starting point was British India. A shadowy undeclared war followed. Among the players in this new Great Game were British spies, Communist revolutionaries, Muslim visionaries and Chinese warlords - as well as a White Russian baron who roasted his Bolshevik captives alive. Here is an extraordinary tale of intrigue and treachery, barbarism and civil war, whose violent repercussions continue to be felt in Central Asia today.
Keywords: History